Case Report: Temozolomide Treatment of Refractory Prolactinoma Resistant to Dopamine Agonists - Tang, Hao; Cheng, Yijun; Huang, Jinyan; Li, Jianfeng; Zhang, Benyan; Wu, Zhe Bao (Frontiers in Endocrinology, 2021)
Therapeutic agents for refractory prolactinomas that are resistant to dopamine agonists (DAs) are troublesome, and surgery often only removes a large part of the tumor without complete remission. Among the various second-line treatment regimens, the treatment effect of the alkylating agent temozolomide (TMZ) is only effective for approximately half of patients; however, complete remission is rare. Here we report a patient with prolactinoma who was resistant to high-dose cabergoline (CAB) treatment, demonstrating a continuous increase in both the tumor volume and the prolactin (PRL) level. Given that this case is a refractory prolactinoma, the patient underwent two transsphenoidal approach (TSA) surgeries. The pathological analysis indicated that the Ki-67 index increased significantly from 3% to 30%, and the expression levels of DRD2 and MGMT were low. Finally, TMZ treatment was recommended. A total of six cycles of TMZ standard chemotherapy shrank the tumor volume and the tumor disappeared completely. During the 6-month follow-up period, the tumor did not relapse again, and the PRL level was also normal. RNA sequencing and DNA whole genome sequencing were performed on this prolactinoma specimen, revealing 16 possible gene mutations, including a missense mutation of the PABPC1 gene. Additionally, the copy number variation analysis results showed that several chromosomes had copy number gains compared to the matched peripheral blood sample. In this case, low expression of DRD2 and high proliferation led to resistance to CAB, whereas low MGMT expression contributed to sensitivity to TMZ treatment. The results of genome sequencing still need further investigation at the molecular level to explain the tumor aggressiveness and high sensitivity to TMZ.